ANALISIS KEKUATAN STRUKTUR TRUCK MOUNTED CRANE MENGGUNAKAN METODE ELEMEN HINGGA - Muhammad Al Hazman; Alwi Sina Khaqiqi; Indri Ika Widyastuti; Muhammad Rizki Andika Saputra; Nur Imam Prakoso Ramadhani; Siti Rahayuningsih (Universitas Muhammadiyah Surabaya, 2026)
Truck mounted crane is a tool used to move objects from one place to another within a limited operating range with the advantage of heavy load mobilization and cargo carrying capacity in one vehicle unit. The crane on the truck is equipped with long arms that can be extended or shortened automatically to adjust to needs, and can adjust the height by changing the elevation angle. This study examines the analysis of the strength of the crane boom in two scenarios of 8.178 meters and 5.478m using the finite element method. In each test scenario, four variations of elevation angles were carried out, namely, 90°, 100°, 110°, and 120°, and carried three variations of loads, namely, 2 tons, 2.5 tons, and 3 tons. In the first scenario with a length of 8.178 meters, the largest deformation was obtained when loading 3 tons and an elevation angle of 90°, the largest von misses value was obtained when loading 3 tons and an angle of 120°, and the largest safety factor was obtained when loading 2 tons and an angle of 90°. Meanwhile, in the second scenario with a crane boom length of 5.478 meters, the largest deformation was obtained when loading 3 tons and an angle of 90°, the largest von misses value was obtained when loading 3 tons and an angle of 120°, and the largest safety factor was obtained when loading 2 tons and an angle of 90°.